Differentiated Instruction in Improving Students’ Task-persistence in Inclusive Education Settings: The Mediating Effects on Prior-achievement Gaps - Charity Neejide Onyishi (South Sulawesi Education Development (SSED), 2024)
Increasing emphasis is laid on non-cognitive academic skills such as persistence for explaining and improving learners’ success and progress in learning and achievements. Research shows that poor task-persistence in accountable for poor students’ achievements. This study investigated the effect of differentiated instruction on students’ task-persistence in inclusive Education setting. The study further sought to find out the moderating effects of prior-achievement on mathematics task-persistence of students taught with differentiated instruction compared to those in control condition. The study adopted a pretest-posttest control group quasi-experimental research design involving one experimental group and one control group. A total of 158 Senior Secondary II students and 4 mathematics teachers, from 4 intact inclusive classes participated in the study. Three instruments; Academic Task-persistence Scale (ATPS); Open-ended mathematics task (OEMT) and Prior -Achievement Record Sheet (SPMAS) were used for data collection. Data were analyzed using descriptive statistics and Repeated measures Analysis of Variance (ANOVA). Findings revealed that differentiated instruction significantly improved academic task-persistence of students compared to control condition. Prior-achievement had significant influence on the students’ persistence in mathematic task, which was mediated by DI. It was concluded in the study that differentiated instruction encourages active participation of students and enhances their task-persistence.